NATO defense expenditures in 1949-2017 - Wołkonowski Jarosław (SHS Web of Conferences, 2018)
The article presents the development of the issue of expenditure on the defense of NATO countries. The amount of these expenditures of NATO countries compared to GDP, absolute values and their share in public spending were analyzed. In the years 1949-1992, all NATO countries (except Luxembourg) had defense spending above 2% of GDP. Changes in the international situation at the end of the 20th century in Europe caused a decrease in defense spending below 2% of GDP in the period between 1993 and 2017. Despite the decisions taken in 2006 and 2014, only 5 countries now fulfil this condition. US expenditures in the studied period accounted for 65.5% of the NATO budget.